Developing Supplementary Materials for Fast Learners in 7th Grade Based on the Merdeka Curriculum - Ni Made Sintya Dewi; Putu Kerti Nitiasih; Putu Eka Dambayana (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study aims to develop supplementary English teaching materials for seventh-grade fast learners based on the Independent Curriculum. This study uses the Design and Development (DnD) method proposed by Richey and Klein, which includes four stages: analysis, design, development, and evaluation. The research subjects involved an English teacher and seventh-grade students at SMP Negeri 6 Singaraja, Buleleng Regency. Data collection was conducted through observation, interviews, questionnaires, and document analysis. The supplementary teaching materials developed used three learning approaches: problem-based learning, project-based learning, and discovery-based learning. The results of expert assessments showed that the developed teaching materials were in the very good category and were declared suitable for use in classroom learning. The findings of this study indicate that the supplementary teaching materials are able to meet the needs of fast learners and support the implementation of the Independent Curriculum. This research contributes to the development of teaching materials that are appropriate to the characteristics of fast learners and support more effective and enjoyable learning.